TELECARE CENTRAL: NURSING INTERVENTION PERSPECTIVE. - Mello Delphino Machado, Tallita; Ferreira Santana, Rosimere; Serra Hercules, Ana Beatriz (Cogitare Enfermagem, 2020)
Objective: To report the development and applicability of a Telecare Central as a nursing intervention. Method: A descriptive experience-report-type study of a technological project financed for the creation of a communication and information technology network for the telephone follow-up of adults and the elderly, using online software to carry out the interventions. Results: The information system enabled telephone intervention in a systematized manner, as well as the storage of the collected data. In the example adopted (follow-up of a facectomy), there was an increased demand for guidance on the 1st and 4th postoperative days regarding discomfort control, use of the eye patch, cleaning of the operated eye, use of eye drops, use ofglasses and guidance on self-care. Conclusion: The telephone follow-up by the nurse favors continuity of the home care measures.